NS4/5 mutations enhance flavivirus Bamaga virus infectivity and pathogenicity in vitro and in vivo - Colmant, Agathe M. G. (PLoS Negl Trop Dis, 2020)
Flaviviruses such as yellow fever, dengue or Zika viruses are responsible for significant human and veterinary diseases worldwide. These viruses contain an RNA genome, prone to mutations, which enhances their potential to emerge as pathogens. Bamaga virus (BgV) is a mosquito-borne flavivirus in the yellow fever virus group that we have previously shown to be host-restricted in vertebrates and horizontally transmissible by Culex mosquitoes. Here, we aimed to characterise BgV host-restriction and to investigate the mechanisms involved. We showed that BgV could not replicate in a wide range of vertebrate cell lines and animal species. We determined that the mechanisms involved in BgV host-restriction were independent of the type-1 interferon response and RNAse L activity. Using a BgV infectious clone and two chimeric viruses generated as hybrids between BgV and West Nile virus, we demonstrated that BgV host-restriction occurred post-cell entry. Notably, BgV host-restriction was shown to be temperature-dependent, as BgV replicated in all vertebrate cell lines at 34°C but only in a subset at 37°C. Serial passaging of BgV in Vero cells resulted in adaptive mutants capable of efficient replication at 37°C. The identified mutations resulted in amino acid substitutions in NS4A-S124F, NS4B-N244K and NS5-G2C, all occurring close to a viral protease cleavage site (NS4A/2K and NS4B/NS5). These mutations were reverse engineered into infectious clones of BgV, which revealed that NS4B-N244K and NS5-G2C were sufficient to restore BgV replication in vertebrate cells at 37°C, while NS4A-S124F further increased replication efficiency. When these mutant viruses were injected into immunocompetent mice, alongside BgV and West Nile virus chimeras, infection and neurovirulence were enhanced as determined by clinical scores, seroconversion, micro-neutralisation, viremia, histopathology and immunohistochemistry, confirming the involvement of these residues in the attenuation of BgV. Our studies identify a new mechanism of host-restriction and attenuation of a mosquito-borne flavivirus.